2011
DOI: 10.1371/journal.pone.0023712
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Detection of Proteins Retro-Translocated from the ER to the Cytosol by In Vivo Biotinylation

Abstract: Retro-translocation from the ER to the cytosol of proteins within the secretory pathway takes place on misfolded molecules that are targeted for degradation by the cytosolically located 26S proteasome complex. Retro-translocation occurs also for other proteins (such as calreticulin) that, despite being synthesized and transported to the ER, are in part dislocated to the cytosol. We have taken advantage of the E. coli derived biotin-ligase (BirA) expressed in the cytosol of mammalian cells to specifically bioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…We found that for both proteins, a fraction of the biotinylated molecules retain their glycosylation state, in agreement with previous findings (11,53) and consistent with the fact that the deglycosylating activity in mammalian cells is provided by the cytosolic PNGase (54). This confirms that deglycosylation appears to be the rate-limiting step of the process because deglycosylated biotinylated material only accumulates upon proteasomal inhibition, whereas glycosylated biotinylated molecules are also detected without inhibition.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that for both proteins, a fraction of the biotinylated molecules retain their glycosylation state, in agreement with previous findings (11,53) and consistent with the fact that the deglycosylating activity in mammalian cells is provided by the cytosolic PNGase (54). This confirms that deglycosylation appears to be the rate-limiting step of the process because deglycosylated biotinylated material only accumulates upon proteasomal inhibition, whereas glycosylated biotinylated molecules are also detected without inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…In this assay denatured samples are run in the presence of StrAv, causing retardation only of biotinylated molecules (30). As demonstrated previously for other proteins (11), all of the biotinylated CD4 and Tetherin found in cells expressing cyt-BirA corresponds to molecules that have been retro-translocated to the cytosol.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations